Interpreting growth hormone and IGF-I results using modern assays and reference ranges for the monitoring of treatment effectiveness in acromegaly - Clemmons, David R.; Bidlingmaier, Martin (Frontiers in Endocrinology, 2023)
Standard treatment for acromegaly focuses on the achievement of target absolute levels of growth hormone (GH) and insulin-like growth factor (IGF-I). The appropriateness of these targets when measured using modern assay methods is not well defined. This paper reviews biochemical status assessed using methods available at the time and associated clinical outcomes. GH measurements were shown to provide an indication of changes in tumor size, and failure of GH suppression after glucose stimulation is associated with tumor recurrence. IGF-I levels were more closely associated with changes in symptoms and signs. Reduced GH and IGF-I concentrations were shown to be associated with increased longevity, although the degree of increase has only been analyzed for GH. Lowering of GH and IGF-I has consistently been associated with improved outcomes; however, absolute levels reported in previous studies were based on results from methods and reference ranges that are now obsolete. Applying previously described absolute thresholds as targets (e.g. “normal” IGF-I level) when using current methods are best applied to those with active acromegaly symptoms who could benefit from further lowering of biochemical markers. In asymptomatic individuals with mild IGF-I or GH elevations, targeting biochemical “normalization” would result in the need for combination pharmacotherapy in many patients without proven benefit. Measurement of both GH and IGF-I remains an essential component of diagnosis and monitoring the effectiveness of treatment in acromegaly; however, treatment goals based only on previously identified absolute thresholds are not appropriate without taking into account the assay and reference ranges being employed. Treatment goals should be individualized considering biochemical improvement from an untreated baseline, symptoms of disease, risks, burdens and costs of complex treatment regimens, comorbidities, and quality of life.